DIFFERENTIATED EFFECTS OF GLUCOSAMINYLMURAMILDIPEPTIDE ON THE NONTRANSFORMED AND EXPERIMENTALLY TRANSFORMED PHENOTYPE OF CD62L+CD63+CD66d+ NEUTROPHILIC GRANULOCYTES IN CONVENTIONALLY HEALTHY PEOPLE - I. V. Nesterova (SPb RAACI, 2018)
Modern studies have shown a high plasticity and phenotypic diversity of neutrophilic granulocytes (NG) provided by different receptors, which are diagnostic markers for the functional capacity of the cell in the course of their activities. We investigated NG from peripheral  blood, obtained from healthy people of both sexes aged from 26 to 66 years. Evaluation of the neutrophil membrane receptor expression was carried out by flow cytometry. The relative amount of neutrophilic granulocytes expressing membrane CD62L, CD63, CD66d receptors and the intensity of their expression were  determined according to their fluorescence intensities. The surface NG membrane receptors, i.e., CD62L, CD63, CD66d were studied upon the in vitro experimental influence of the following bacterial peptides: N-formyl-methionyl-leucyl-phenylalanine (FMLP, model 1); glucosaminylmuramyldipeptide (GMDP, model 2), and simultaneous incubation of NG blood with fMLP and GMDP (model 3). The in vitro treatment with fMLP in the in vitro model was used to transform the NG phenotype of conventionally healthy subjects, expressing CD62, CD63, CD66d molecules. The treatment caused a significantly decrease in both CD62L and the CD62L expression in relative amounts of neutrophilic granulocytes with a parallel increase of CD63 expression density. The effect of GMDP on the NG phenotype of conditionally healthy subjects did not change the amount of CD62L+NG and CD63+NG, and did not affect CD62L and CD63 expression density on the surface of NG. However, the amount of CD66d+NG was significantly increased with the unchanged expression of CD66d molecules. GMDP introduced together with the bacterial fMLP peptide was shown to neutralize some features of the NG phenotype transformation caused by fMLP, i.e., the amount of CD62L+ NG was restored by 22 % and the CD62L expression density increased significantly. At the same time, GMDP did not correct the negative effect of fMLP upon the number of CD63+NG and CD66d+NG, and on the CD63 and CD66d expression. Simultaneous addition of fMLP  and GMDP did significantly increase the amount of CD66d+NG and expression density of CD63 molecules on the CD63+NG membrane as compared to intact NG of conditionally healthy subjects. The obtained data are important in order to justify some new immunotherapeutic strategies aimed at correction of the negatively transformed NG phenotype, which accompanies some infectious and inflammatory diseases of bacterial etiology with atypical clinical course.